Psychological symptoms as long-term consequences of war experiences - Priebe, Stefan (Array, 2013)
War experiences can affect mental health, but large-scale studies on the long-term impact are rare. We aimed to assess long-term mental health consequences of war in both people who stayed in the conflict area and refugees. On average 8 years after the war in former Yugoslavia, participants were recruited by probabilistic sampling in 5 Balkan countries and by registers and networking in 3 Western European countries. General psychological symptoms were assessed on the Brief Symptom Inventory and posttraumatic stress symptoms on the Impact of Event Scale-Revised. We assessed 3, 313 interviewees in the Balkans and 854 refugees. Paranoid ideation and anxiety were the severest psychological symptoms in both samples. In multivariable regressions, older age, various specific war experiences and more traumatic experiences after the war were all associated with higher levels of both general psychological and posttraumatic stress symptoms in both samples. Additionally, a greater number of migration stressors and having only temporary legal status in the host country were associated with greater severity of symptoms in refugees. Psychological symptoms remain high in war-affected populations many years after the war, and this is particularly evident for refugees. Traumatic war experiences still predict higher symptom levels even when the findings have been adjusted for the influence of other factors.